How entrepreneurial SMEs compete through digital platforms : the roles of digital platform capability, network capability and ambidexterity - Cenamor, Javier; Parida, Vinit; Wincent, Joakim (Elsevier, 2019)
Digitalization offers unprecedented opportunities for entrepreneurial small and medium-sized enterprises (SMEs). However, many entrepreneurial SMEs lack resources and capabilities or suffer from inertia, which hampers these opportunities. This study investigates how entrepreneurial SMEs can enhance performance through digital platforms. Specifically, the study examines the effect of digital platform capability and network capability on entrepreneurial SMEs' financial performance. The study also examines how exploitation and exploration orientations moderate this relationship. Based on analysis of 230 entrepreneurial SMEs, the results indicate that digital platform capability has a positive indirect effect on entrepreneurial SMEs' performance via network capability. The study also shows that exploitation and exploration orientations negatively and positively moderate this effect, respectively. The results suggest that entrepreneurial SMEs can enhance their performance through digital platform capability by aligning this capability with their orientation. These findings thereby enrich the literature on entrepreneurial SMEs and capabilities.
Keywords: entrepreneurship; digitalization; Innovation management; entrepreneurial small and medium-sized enterprises; fi=Johtaminen ja organisaatiot|en=Management and Organization|